Problem of Social Responsibility of Laboratory Sciences - Sikora, Marek (Ruch Filozoficzny, 2022)
The classic approach to science is dominated by the belief that science is a form of cognitive activity that focuses on constructing theories to describe and explain the phenomena and processes found in the world. Due to the fulfilment of the criteria of intersubjective communicability and controllability, theories are considered to be objective products of research activity that do not bear social responsibility for their applications. In this paper, the issue of social responsibility of science is addressed both from the classic perspective and from the non-classic viewpoint represented by laboratory sciences, i.e. those sciences that are predominantly concerned with creating phenomena rather than discovering them. It is argued that whereas in the former case the problem of social responsibility of science does not provoke serious controversy, in the latter case such controversies do exist and, furthermore, they are justified.